The changing landscape of stage III lung cancer: a literature review. Issue 8 (2nd August 2020) - Patel, Monaliben; Bruno, Debora; Grubb, William; Biswas, Tithi
ABSTRACT: Introduction: The treatment of stage III non-small cell lung cancer (NSCLC) remains challenging and associated with overall poor outcomes. Since seminal studies in the early 90s introduced concurrent chemo-radiotherapy as standard of care for treatment of this disease, no major advances have been introduced in this landscape. Both radiation dose escalation and neoadjuvant/adjuvant chemotherapy strategies were unsuccessful to improve the survival over standard of care radiation dose and chemotherapy schedule: five-year overall survival (OS) ranging from 15–20%. However, in 2017 the PACIFIC Trial demonstrated that the addition of consolidative immune checkpoint inhibitor durvalumab for 1 year led to superior progression-free survival (PFS) and 3-year overall survival with no significant increase in toxicity compared to placebo in patients who achieved disease control with concurrent chemo-RT. Areas covered: This article reviews the treatment evolution of stage III NSCLC over the past decades, discusses current standard of care strategies, and highlights potential future directions for the management of this condition. Expert opinion: Ongoing trials incorporating upfront checkpoint inhibitors with radiotherapy will answer whether adding checkpoint inhibitors to chemotherapy or substituting them for chemotherapy altogether will improve long-term outcome.